2021
DOI: 10.3389/fphar.2021.701087
|View full text |Cite
|
Sign up to set email alerts
|

Magnoflorine Alleviates “M1” Polarized Macrophage-Induced Intervertebral Disc Degeneration Through Repressing the HMGB1/Myd88/NF-κB Pathway and NLRP3 Inflammasome

Abstract: Intervertebral disc degeneration (IDD) is related to the deterioration of nucleus pulposus (NP) cells due to hypertrophic differentiation and calcification. The imbalance of pro-inflammatory (M1 type) and anti-inflammatory (M2 type) macrophages contributes to maintaining tissue integrity. Here, we aimed to probe the effect of Magnoflorine (MAG) on NP cell apoptosis mediated by “M1” polarized macrophages. THP-1 cells were treated with lipopolysaccharide (LPS) to induce “M1” polarized macrophages. Under the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 45 publications
1
33
0
1
Order By: Relevance
“…However, previous studies often tested in the inflammatory environment, which probably induce macrophage polarization and make the results ambiguous in some extend. A recent study by Li et al revealed M1 macrophage polarization induced IDD (29), and M2a macrophages promote ECM metabolic imbalances in rat IDD (30). Nonetheless, the spectrums of macrophages that mimic actual environment of IDD are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies often tested in the inflammatory environment, which probably induce macrophage polarization and make the results ambiguous in some extend. A recent study by Li et al revealed M1 macrophage polarization induced IDD (29), and M2a macrophages promote ECM metabolic imbalances in rat IDD (30). Nonetheless, the spectrums of macrophages that mimic actual environment of IDD are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 inflammasome has been found to be implicated in multiple inflammatory diseases, including Alzheimer's disease, atherosclerosis, diabetes, and various infectious diseases . Hence, targeting the NLRP3 (Zhao et al, 2021). Moreover, it has been reported that α-mangostin has the ability to regulate NLRP3 inflammasome activity.…”
Section: Discussionmentioning
confidence: 99%
“…Morin was shown to attenuate pyroptosis of NPCs and ameliorate IDD via inhibiting the NLRP3/caspase‐1/IL‐1β signaling pathway (Zhou et al, 2021). Additionally, magnoflorine was reported to alleviate IDD progression through inhibiting inflammation, cell apoptosis, and matrix degradation via repressing NLRP3 inflammasome activity (Zhao et al, 2021). Moreover, it has been reported that α‐mangostin has the ability to regulate NLRP3 inflammasome activity.…”
Section: Discussionmentioning
confidence: 99%
“…На экспериментальной модели аутоиммунного миокардита также было установлено репрограммирование клеток в сторону М1-макрофагов путем активации пути TLR4-PI3Kγ-Erk1/2 под действием HMGB1 [26]. Ингибирование HMGB1 в свою очередь способно снизить количество провоспалительных макрофагов [12,38]. Все это может свидетельствовать в пользу того, что HMGB1 является одним из каузальных факторов обнаруженных нами изменений в субпопуляционном составе моноцитов.…”
Section: Discussionunclassified